Enhancing Teaching and Supervisory Staff’s Creative Problem-Solving Skills - Mai Charoentham; Thiyaporn Kantathanawat; Paitoon Pimdee; Kwantisara Apisuksakul (Emerging Science Journal, 2025)
This research analyzed creative problem-solving (CPS) components and examined the perceptions of Thai educational personnel regarding their CPS abilities. The sample consisted of 534 primary school teachers and educational supervisors during the 2024 academic year, selected through multistage random sampling. Data were collected using a questionnaire assessing CPS skills, which were then analyzed using means (M), standard deviations (SD), and second-order confirmatory factor analysis (CFA). The research revealed that the second-order CFA model for CPS among educational personnel (teachers and supervisors) consists of five key components. Ranked from highest to lowest, these were educators' perceptions of their CPS abilities to solve problems (SOL) (M = 4.23, SD = 0.54), ability to identify problems (IDE) (M = 4.17, SD = 0.57), ability to create knowledge (CRE) (M = 4.17, SD = 0.59), ability to discover concepts (INS) (M = 4.12, SD = 0.58), and ability to discover methods to solve problems (MET) (M = 4.11, SD = 0.58). The model strongly aligned with empirical data, indicating that all three models exhibited positive component weights (β) that were statistically significant at the .01 level. This finding underscores the strength of the CPS framework for educational personnel. These findings provide compelling evidence for the effectiveness of the proposed model in assessing and enhancing CPS skills among educational professionals, contributing valuable insights to both practice and future research in this field. This study fills a gap in the literature by providing empirical evidence on the CPS capabilities of educational personnel.
Keywords: Mathematics Education and Pedagogy; Technology-Enhanced Education Studies; Sports and Physical Education Research